Effect of Water Cinnamon Extract on Mutans Streptococci , in Comparison to Chlorhexidine Gluconate and Zac (In Vitro and In Vivo Study) (Mustansiria Dental Journal, 2018)
Background:The purpose of this study was to evaluate the effect of different concentrations of water cinnamon extract on growth of mutans streptococci, in comparison to chlorhexidine gluconate (0.2%), Zac [0.12% chlorhexidine with 0.05% sodium fluoride (Maleh Chemical products, Syria)] and deionized water in vitro and viability counts of mutans streptococci among a number of volunteers.Material and Methods:Stimulated saliva was collected from six healthy looking students aged (22-24) from which mutans streptococci were isolated. Sensitivities of mutans streptococci according to Agar Well Technique showed that mutans streptococci were more sensitive to chlorhexidine and Zac compared to water cinnamon extract. The effect of these agents on the viability counts of mutans streptococci in comparison to the control in vitro were studied, a significant reduction in the counts of bacteria at concentrations 20% of water cinnamon extract was illustrated (P